2020
DOI: 10.1186/s12967-020-02220-3
|View full text |Cite
|
Sign up to set email alerts
|

Whole transcriptional analysis identifies markers of B, T and plasma cell signaling pathways in the mesenteric adipose tissue associated with Crohn’s disease

Abstract: Background: Crohn's disease (CD) is a multifactorial disease characterized by chronic intestinal inflammation. The increased visceral adiposity near the affected intestinal area, of which mesenteric adipose tissue (MAT) is the main component, is a feature of CD. Both protective and pathological roles have been attributed to this disease-associated tissue in CD. To understand the contribution of MAT to CD pathophysiology, a molecular and cellular signature of disease-associated MAT in CD patients was provided. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 50 publications
2
19
0
2
Order By: Relevance
“…Meanwhile, the same up-regulation of DERL3 was found in RA synovial tissues from the proteomics data and the mRNA level. And DERL3 is also found as plasma cell or B cell signature genes [42,43]. All these research results and our results suggested that there might be more B cell in RA synovial tissues than OA synovial tissues.…”
Section: Discussionsupporting
confidence: 74%
“…Meanwhile, the same up-regulation of DERL3 was found in RA synovial tissues from the proteomics data and the mRNA level. And DERL3 is also found as plasma cell or B cell signature genes [42,43]. All these research results and our results suggested that there might be more B cell in RA synovial tissues than OA synovial tissues.…”
Section: Discussionsupporting
confidence: 74%
“…Moreover, mesenteric adipocytes may, by their production of key chemokines in response to inflammatory/bacterial stimuli, arrange the formation of tertiary lymphoid organs rich in both T- and B- memory cells as well as plasma cells [ 54 ]. Whole transcriptional analysis also supports the role of CD-associated MAT as a site for T-, B-, and plasma cells activation, which suggests that it could act as a reservoir of memory immune response [ 55 ].…”
Section: Adipose Tissue As An Active Endocrine Organ Visceral Adipose Tissue and Ibdmentioning
confidence: 90%
“…7,8 Originally, this increased immune presence was attributed to the local inflammatory environment, and potentially to the effects of translocated intestinal bacteria. [5][6][7][8][9] In addition, an early study described alterations in mesenteric levels of PPAR gamma, prior to the development of morphological abnormalities, suggesting a potential role in disease development rather than just a response. 3 More recent data suggest the accumulation of immune cells may not only be the result of an increased influx of cells, but may also stem from decreased leucocyte egress due to impaired lymphatic flow.…”
Section: Mesentery As Inflammatory Contributormentioning
confidence: 99%